169k views
1 vote
Assignment

Use the function f(x) = 2x3 - 3x2 + 7 to complete the exercises.
f(-1) =
f(1) =
f(2)=
>

User Channy
by
5.0k points

2 Answers

4 votes

Answer:

The value of the function f(x) at x=a can be determined by substituting a instead of x into the function expression.

1. When x=-1, then

f(-1) = 2 * (-1)^3 - 3 * (-1)^2 + 7 = -2 - 3 + 7 = 2.

2. When x=1, then

f(1) = 2 * 1^3 - 3 * 1^2 + 7 = 2 - 3 + 7 = 6.

3. When x=2, then

f(-1) = 2 * 2^3 - 3 * 2^2 + 7 = 16 - 12 + 7 = 11.

Explanation:

User RedFox
by
5.6k points
6 votes

Answer:

f(−1) =✔ 2

f(1) = ✔ 6

f(2) =✔ 11

Explanation:

User Ben Aaronson
by
5.4k points